LncRNA MEG3 expression in sepsis and its effect on LPS-induced macrophage function - Pan, Xinrong; He, Lingling (Cellular and Molecular Biology, 2020)
Sepsis is a dangerous disease that is caused by an overreaction of the body’s immune system to infection and gradually spreads throughout the body. This experiment was carried out to explore the expression of LncRNA MEG3 in sepsis and its effect on LPS-induced macrophage function. Methods 60 sepsis patients admitted to our hospital from February 2017 to September 2018 were selected as the sepsis group, and 50 non-septic patients diagnosed and treated in our hospital during the same period were selected as the control group. qRT-PCR was used to detect the expression level of MEG3. ROC curve was used to analyze the diagnostic value of serum MEG3 in sepsis. The human macrophage cell line U937 was cultured in vitro and randomly divided into NC group, LPS group, LPS + pcDNA group, and LPS + pcDNA-MEG3 group. Flow cytometry was applied to detect the apoptosis rate. The levels of IL-1Î² and TNF-Î± were detected by ELISA. Western blot was used to detect the expression of Bax, Bcl-2 and NF-ÎºB signaling pathway-related proteins p65 and p-p65. Results: The expression level of serum MEG3 in the sepsis group was significantly lower than that in the control group (P <0.05). ROC curve analysis showed that the AUC area was 0.856, the sensitivity was 0.700, and the specificity was 0.883. Compared with the NC group, the macrophage apoptosis rate in the LPS group was increased (P <0.05), the levels of Bax and p-p65 protein were significantly increased (P <0.05), and the level of Bcl-2 protein was decreased (P <0.05), the levels of IL-1Î² and TNF-Î± were increased (P <0.05). Compared with the LPS + pcDNA group, the apoptosis rate of the LPS + pcDNA-MEG3 group was significantly reduced (P <0.05), the levels of Bax and p-p65 protein were reduced (P <0.05), and the level of Bcl-2 protein was significantly increased (P <0.05), the levels of IL-1Î² and TNF-Î± were reduced (P <0.05). Conclusion: The low expression of LncRNA MEG3 in the serum of patients with sepsis can predict the occurrence of sepsis. Overexpression of MEG3 can inhibit LPS-induced macrophage apoptosis and secretion of inflammatory factors by inhibiting the activation of the NF-ÎºB signaling pathway.